Obesity in the Russian population during the COVID-19 pandemic and associated factors. Data from the ESSE-RF3 study - Yu. A. Balanova; O. M. Drapkina; V. A. Kutsenko; A. E. Imaeva; A. V. Kontsevaya; S. A. Maksimov; G. A. Muromtseva; M. B. Kotova; N. S. Karamnova; S. E. Evstifeeva; A. V. Kapustina; O. A. Litinskaya; et al. (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To study the problem of obesity at the national level.Material and methods. The ESSE-RF3 study examined a representative sample of the population of 15 Russian regions aged 35-74 years with a response >70% (n=28731). Modular design questionnaire was used. The study received approval from the Independent Ethics Committee of the National Medical Research Center for Therapy and Preventive Medicine. Signed informed consent was obtained from each participant. Body mass (BM) was measured once with an accuracy of 100 g. The height was measured with an accuracy of 0,5 cm once in a standing position without shoes. Waist circumference was measured with a standard measuring tape with an accuracy of 0,5 cm. There were following BM categories: insufficient (BM index (BMI) <18,5), normal (18,5≲ BMI ≲24,9), overweight (25,0≲ BMI ≲29,9), class I obesity (30,0≲ BMI ≲34,9), class II obesity (35,0≲ BMI ≲39,9) and class III obesity (BMI >40). Abdominal obesity (AO) was assessed using the following criteria: waist circumference ≥102 cm and ≥88 cm for men and women, respectively. The changes of obesity were studied with the inclusion of materials from the ESSE-RF (2012-14) and ESSE-RF2 (2017) studies, carried out using the same methodology with ESSE-RF3 in the same age range of 35-64 years. Statistical analysis was carried out using the open-source R 3.6.1 environment. Analysis of associations between factors and a binary variable was carried out using the logistic regression method. The significance level for all tested hypotheses was 0,05.Results. Mean BMI values is 28,2±4,6 kg/m2 among men and 28,9±5,9 kg/m2 among women. The prevalence of overweight is 44,0 and 33,7%, obesity — 30,0 and 39,5%, AO — 30,9 and 55,1% among men and women, respectively. In addition, 30,3% have a combination of obesity and AO; obesity and/or AO — 49,1%. Obesity statistics did not significantly change, but in each section the rates are higher among women. The closest associations were found between obesity and hypertension (men: odds ratio (OR) (95% confidence interval) 2,88 (2,66-3,12), women: OR 3,03 (2,81-3,27) (p<0,001) and hyperuricemia for women (OR 4,21 (3,74-4,75) (p<0,001).Conclusion. A third of the Russian population is obese, and half has obesity and/or AO. This severity of the problem requires the development and adoption of a strategy to monitor obesity at the national level.